The role of 18F-FDG PET/CT in Neurolymphomatosis: A Comprehensive Imaging Approach - Sharjeel Usmani; Anjali Jain; Khulood Al Riyami; Najeeb Ahmed; Rashid Al-Sukaiti; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2024)
Neurolymphomatosis (NL) is an uncommon and rare neurologic disorder characterised by extranodal lymphoma, where the tumour cells invade the cranial nerves, nerve plexus, nerve root, spinal nerve roots, trunk nerves or peripheral nerves. MRI is the modality of choice, but is often challenging in detection of early recurrence, assessing residual disease and response evaluation. 18F-FDG PET/CT has superior diagnostic performance compared with body CT in the evaluation of NL. 18F-FDG PET-CT is helpful in evaluation of disease extent and potential to guide biopsy. 18F-FDG PETCT is a highly sensitive technique for early localisation of NL than MRI or CT alone. Besides diagnostic and prognostic value in NL, it might be very helpful in response assessment. Key Words: 18F-FDG PET/CT; Neurolymphomatosis; peripheral nervous system.